Causal association between air pollution and frailty: a Mendelian randomization study - Xiao, Haixia; Huang, Shan; Yang, Wei; Zhang, Wenni; Xiao, Huanshun; Cai, Shuangming (Frontiers in Public Health, 2023)
Backgrounds: Frailty is a significant problem for older persons since it is linked to a number of unfavorable consequences. According to observational researches, air pollution may raise the risk of frailty. We investigated the causal association between frailty and air pollution (including PM2.5, PM2.5-10, PM10, nitrogen dioxide, and nitrogen oxides) using Mendelian randomization approach.We conducted MR analysis using extensive publically accessible GWAS (genome-wide association studies) summary data. The inverse variance weighted (IVW) method was employed as the primary analysis method. The weighted median model, MR-Egger, simple model, and weighted model approaches were chosen for quality control. The Cochran's Q test was utilized to evaluate heterogeneity. Pleiotropy is found using the MR-Egger regression test. The MR-PRESSO method was used to recognize outliers. The leave-one-out strategy was used to conduct the sensitivity analysis.Results: MR results suggested that PM2.5 was statistically significantly associated with frailty (odds ratio (OR)=1.33; 95%confidence interval (CI)= 1.12-1.58, P=0.001) in IVW method. We observed no statistical association between PM2.5-10(OR = 1.00, 95% CI = 0.79-1.28, P = 0.979), PM10(OR = 0.91, 95% CI = 0.75-1.11, P = 0.364), nitrogen dioxide(OR = 0.98, 95% CI = 0.85-1.12, P = 0.730), nitrogen oxides(OR = 1.15, 95% CI = 0.98-1.36, P = 0.086) and frailty. There was no pleiotropy in the results. The sensitivity analysis based on the leave-one-out method showed that the individual single nucleotide polymorphisms(SNPs) did not affect the robustness of the results.The current MR investigation shows a causal association between PM2.5 and frailty. Frailty's detrimental progression may be slowed down with the help of air pollution prevention and control.